Higher prevalence of short stature and excess weight in children with sleep disorders - Halabi, Inbal; Hadar, Dana; Cohen, Hilla; Rakover, Yardena Tenenbaum; Pillar, Giora (Frontiers in Endocrinology, 2025)
BackgroundSleep disorders are common in childhood and are recognized as a significant public health concern, particularly due to their association with childhood obesity. However, their impact on growth disturbances has been only minimally explored. In the present study, we investigate the association between sleep disorders and linear growth and excess weight in children.Study DesignData were collected retrospectively (January 2012–December 2022) from computerized medical records of 3,210 patients (newborn–18 years) diagnosed with sleep disorders who underwent sleep analysis at the Sleep Clinic of Carmel Medical Center. A control group (n =12,840), matched for age and ethnic background, was selected from the same healthcare database. Additionally, subgroup analyses were performed by sex and across three age groups.ResultsA higher rate of short stature, defined as height at or below the 3rd percentile, was observed in the study group compared to controls (8.66% vs. 6.25%, p < 0.001). This difference was primarily seen in the 0–6 years age group (girls: OR 1.49, p = 0.003; boys: OR 1.57, p < 0.001). The diagnosis of short stature and growth hormone deficiency was documented in 10.1% and 2.1% of the study group, respectively, compared to 7.5% and 1.15% in the control group (p < 0.001 for both). Rates of overweight and obesity were higher among children in the study group compared to controls (overweight: 25.9% vs. 22.2%; obesity: 14.6% vs. 10.4%; p < 0.001). This difference was primarily observed in children aged 6–18 years, with the strongest effects seen in adolescent boys. Notably, children with obstructive sleep apnea had a significantly higher prevalence of short stature compared to those with other sleep disorders (13.4% vs. 7.7%; p < 0.001).ConclusionsOur findings of a higher prevalence of growth disturbances and excess weight among children with sleep disorders highlight the importance of early recognition and timely intervention for pediatric sleep disorders. Such measures may improve sleep quality and daily functioning and potentially benefit growth and weight outcomes.